Age-related characteristics of sedation in pediatric patients and their correlated adverse events: a cohort study - Nong, Xiaoling; Lu, Yixing; Jiang, Wenqing; Qin, Yanlv; Jing, Shunzhong; Chi, Tao; Peng, Wei; Liu, Siyan; Lin, Yunan (Frontiers in Pediatrics, 2024)
ObjectiveThe objective of this research was to examine the features and potential hazards of sedation in children of varying ages. Additionally, the study aimed to comprehend these variations to enhance the safety and efficacy of clinical applications.MethodsA retrospective analysis was conducted on case data involving pediatric patients who underwent imaging procedures in outpatient settings and necessitated procedural sedation from 2022 to 2024. The research participants were categorized into three age groups: ≤1 year, 1–3 years, and 3–12 years. The primary sedative agents administered were oral midazolam in conjunction with intranasal dexmedetomidine. We examined the effects of sedation and the occurrence of adverse events across various age groups. Additionally, we applied multivariate logistic regression to identify factors linked to these adverse events.ResultsThe study observed 2,194 children, with 879 (40.1%) being ≤1-year-old. The ≤1-year-old group achieved faster sleep onset at 18.7 ± 0.3 min, with no significant variance in awakening time and length of stay among the groups. The incidence of adverse events varied significantly by age, with the highest rate of 12.2% in the ≤1-year-old group and the lowest rate of 9.7% in the 3–12-year-old group. Multivariate analysis revealed age as an independent factor affecting adverse event occurrence, with a relative risk ratio (AOR) of 2.21 (95% CI: 1.31–3.75) for delayed awakening in children ≤1-year-old, 15.03 (95% CI: 1.92–117.61) for hypoglycemia, and a relative risk ratio (AOR) of 4.58 (95% CI: 2.22–9.42) for receiving a significant intervention.ConclusionsSignificant variations in sedation reactions and adverse events were observed across the different age groups. Specifically, children aged ≤1 year exhibited a higher susceptibility to adverse events such as delayed awakening and hypoglycemia. Clinical Trial Registrationchictr.org.cn identifier (ChiCTR2400082774).